2004
DOI: 10.1359/jbmr.040313
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bone Loss in Paraplegics Over 2 Years With Alendronate

Abstract: To assess the effects of long-term treatment of bone loss with alendronate in a group of paraplegic men, 55 patients were evaluated in a prospective randomized controlled open label study that was 2 years in duration comparing alendronate and calcium with calcium alone. Bone loss was stopped at all cortical and trabecular infralesional sites (distal tibial epiphysis, tibial diaphysis, total hip) with alendronate 10 mg daily. Introduction: Bone loss after spinal cord injury (SCI) leads to increased fracture ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 46 publications
(53 reference statements)
4
60
1
4
Order By: Relevance
“…Knowing from the SCI literature that the patients have an increased risk in some specific aspects, for instance osteoporosis [14][15][16] or coronary heart disease, 17 it was decided to adapt the usual up-to-date medical recommendations for prevention to the special situation needed for individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing from the SCI literature that the patients have an increased risk in some specific aspects, for instance osteoporosis [14][15][16] or coronary heart disease, 17 it was decided to adapt the usual up-to-date medical recommendations for prevention to the special situation needed for individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we share the same opinion with Szollar (20), who claimed that control BMD measurements against bone loss should be started within 1 year after the injury, and if the BMD values were close to the osteoporosis margin, treatment should be started in the first year. Zehnder et al (21) reported that, in men with paraplegia, SCI bone loss was stopped at all measured cortical and trabecular infralesional sites over 24 months with alendronate 10 mg daily.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Dual energy X-ray absorptiometry (DEXA) (research based and clinical) confirms a rapid decline in lower extremity bone mineral density (BMD) in the initial 6 to 18 months after injury, resulting in osteopenia and susceptibility for fracture. 17,18,21 Preliminary data suggest that antiresorptive agents (aminobisphosphonates) may ameliorate SCI bone loss. [22][23][24] However, there are still many clinical uncertainties about the optimal time for the initiation of bone loss prevention protocols, and appropriate avenue(s) for early remediation.…”
Section: Introductionmentioning
confidence: 99%